Tecknical Analysis For Dummies A Wiley Brand - Rockefeller, Barbara (New Jersey John Wiley&Sons Inc, 2014)
In this book you'll know why technical analysis doesn't always work, ways to identify crowd behavior and patterns, when to use chart indicator and how to draw a trendline ; you'll also find guidance on transforming channels into forecasts ,tips for measuring momentum and updates that reflect current market conditions
Includes Index
3
Keywords: Investment Analysis; Technical Analysis